2011
DOI: 10.1038/hdy.2011.94
|View full text |Cite
|
Sign up to set email alerts
|

Healing quantitative trait loci in a combined cross analysis using related mouse strain crosses

Abstract: Inbred mouse strains MRL and LG share the ability to fully heal ear hole punches with the full range of appropriate tissues without scarring. They also share a common ancestry, MRL being formed from a multi-strain cross with two final backcrosses to LG before being inbred by brother-sister mating. Many gene-mapping studies for healing ability have been performed using these two strains, resulting in the location of about 20 quantitative trait loci (QTLs). Here, we combine two of these crosses (N¼638), MRL/lprÂ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…In the current study, real progress has been made in narrowing the quantitative trait intervals by use of the (LG,SM) F34 AIL. An important feature of the present work is that QTLs on chromosomes 9, 10, 11, 14 and 18 discovered in earlier studies (Blankenhorn et al, 2009;Cheverud et al, 2012) were confirmed in the AI line, lending further credence to their role in regenerative healing. New QTLs have been identified on chromosomes 1, 7, 12 and 13 in this study.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In the current study, real progress has been made in narrowing the quantitative trait intervals by use of the (LG,SM) F34 AIL. An important feature of the present work is that QTLs on chromosomes 9, 10, 11, 14 and 18 discovered in earlier studies (Blankenhorn et al, 2009;Cheverud et al, 2012) were confirmed in the AI line, lending further credence to their role in regenerative healing. New QTLs have been identified on chromosomes 1, 7, 12 and 13 in this study.…”
Section: Discussionsupporting
confidence: 49%
“…New QTLs have been identified on chromosomes 1, 7, 12 and 13 in this study. Healing QTLs reported by Cheverud et al (2012) on chromosomes 2, 4, 6, 8 and 19 did not show up as significant at the 5% Bonferroni-corrected significance threshold in the present study. However, each of these QTL locations did pass a point-wise 5% threshold appropriate for testing an a priori hypothesis in the F34 generation given the earlier F2 results.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In our studies, we found that decreased Sdf1 expression and diminished recruitment of Cxcr4 + leukocytes promote tissue regeneration. Our results may also explain the statistically significant linkage of the locus containing Sdf1 to regeneration in QTL studies of MRL mice (Cheverud et al 2012). The balance between inflammatory responses and tissue regeneration is likely to be complex and multiphasic.…”
Section: Discussionmentioning
confidence: 48%
“…From prior quantitative trait locus (QTL) mapping studies in MRL mice (Cheverud et al 2012), we identified one locus linked to regenerative capacity that contained the gene for stromal cell-derived factor-1 (Sdf1; also known as Cxcl12). Sdf1 binds to the chemokine receptor Cxcr4, and increased Sdf1-Cxcr4 signaling has been linked to increased fibrosis and scar formation in multiple tissues, including the lung, liver, and heart.…”
mentioning
confidence: 99%